Globalization and United States' Intra-Industry Trade - Leitão, Nuno Carlos (2020)
The recent trend of globalization has given rise to a new paradigm in international economics, i.e. the simultaneous exports and imports of a product within country or a particular industry called intra-industry trade (IIT) or two-way trade. This study examines country-levels determinants of intra-industry trade, in U.S. trade. The manuscript applies a static and dynamic panel data approach. In contrast to previous studies, this paper used a dynamic panel data to solve the problems of serial correlation and endogeneity. The results indicate that IIT occurs more frequently among countries that are similar in terms of factor endowments. We also introduce economic dimension; this proxy confirms the positive effect of IIT. Our results also confirm the hypothesis that trade increases if the transportation costs decrease.